The Fetternear vestments at the Blairs Museum. Issue 2 (15th September 2016) - Davidson, Peter; King, Prue
Abstract : This article illustrates and describes in detail a fine central European chasuble of the late c17 which, together with two dalmatics, 'The Fetternear Vestments, ' were bequeathed to the Diocese of Aberdeen, in 1921 by the Leslie family, many of whom had been distinguished soldiers on the continent and especially in the Empire. After some contextual discussion of the alleged origins of the Leslie family and of their success in Imperial service, the article examines the traditional belief that the vestments, now at the Blairs Museum, Aberdeen, were made for Count James Leslie (c.1621-1694) partly out of Turkish textiles captured in 1683 at the Siege of Vienna. Detailed analysis of the embroidery on the chasuble, especially of the use of metal thread and 'plate, ' demonstrates that the gold work is indeed of Turkish origin, the rest of the needle work central European, and thus makes the case that this extraordinary hybrid object is indeed a votive vestment made for the Catholic Leslies partly from captured Turkish work.